Chemical composition and provenance of Chinese porcelain shards recovered from Old Goa, west coast of India. (August 2017) - Tripati, Sila; Parthiban, G.; Pattan, J.N.; Menezes, Andrew
Abstract: During recent archaeological explorations at Old Goa, west coast of India, twenty three Chinese porcelain shards of the Ming (Middle to late 16th century), Qing (17th century) and late Qing period (late 17th century) have been recovered. In order to understand the nature and source of raw material and kilns, these shards were analysed for major elements with X-ray fluorescence (XRF), trace and rare earth elements by Inductively Coupled Plasma-Mass Spectrometer (ICP-MS). The analysis suggests that porcelain shards are siliceous in nature (SiO2  ~ 70%) and contain high Al2 O3 (21.6%), Rb (388 ppm) and Ba (160 ppm) but have low Sr (48 ppm). This composition suggests that the raw materials used for producing porcelain were silica, kaolinite and sericite which are characteristics of porcelains manufactured in Southern China. Comparatively, high Al2 O3 (kaolinite) content in porcelains of the Qing Dynasty suggest improvement of quality, particularly mechanical strength, of Jingdezhen porcelain. In general, major element composition, trace metals, total rare earth elements (∑ REE-67 ppm) and their chondrite - normalized pattern of the Ming, Qing and late Qing period are nearly similar and appear to be made of identical raw materials. Highlights: The Ming, Qing and Late Qing Dynasties used Silica, Kaolinite and Sericite minerals in manufacturing the Chinese porcelain. During the Qing Dynasty, high Kaolinite content was used to improve the mechanical strength of the porcelain. These porcelains appeared to be manufactured in the Jingdezhen kilns of the Southern China. During the Portuguese regime, Porcelain was brought from China to Old Goa.